Genetic variability of two Nile tilapia strains by microsatellites markers - Moreira, Angela Aparecida; Hilsdorf, Alexandre Wagner Silva; Silva, Juliana Viana da; Souza, Vânia Ribeiro de (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the genetic variability of two Nile tilapia strains (Oreochromis niloticus), Chitralada and Red Stirling, as well as its offsprings submitted to genetic enhancement programs, in intensive systems farming by microsatellites markers. Thirty individuals of each parental strain, 30 crossbred (CH) individuals from Chitralada and Red Stirling strains, and 30 individuals from Red Stirling progeny (RR) were used. Five microsatellites loci were utilized: UNH104, UNH108, UNH118, UNH222 e UNH231. Low values of inbreeding were observed with a negative FIS in both strains and their crossings. Genetic differences between the two strains were detected through FST = 0.131 and RST = 0.130. The parental strains Chitralada and Red Stirling presented 24.4% of genetic distance, which produced 23.5% of hybrid vigor in the CH stock.